A theoretical study of even-even 162-17870Yb isotopes using interacting vector boson model - D. M. Nasef; E. T. Ellafi; S. M. El-Kadi (Âderna Fìzika ta Energetika)
This theoretical study investigates the properties of even-even 162-17870Yb isotopes using the interacting vector boson model (IVBM). Our study focuses on the ground state band and negative parity band energy-level patterns, which provide insights into the shapes and symmetries of these nuclei. Furthermore, we investigate the collective properties of these isotopes, such as rotational and vibrational motion, as well as their interplay. The results of our theoretical analysis shed light on the structural evolution of ytterbium isotopes with increasing neutron numbers. The comparison of our theoretical predictions with experimental data will provide valuable insights into the nuclear structure of these isotopes and help validate the IVBM model's effectiveness in describing collective phenomena. This theoretical study employs the IVBM to investigate the dynamic symmetry of even-even 162-17870Yb isotopes. By conducting tests such as the ratio, backbending, and staggering analyses, we aim to determine the underlying symmetries governing the behavior of these isotopes. These results indicate that 16270Yb possess O(6) symmetry, 164-16670Yb have transition O(6) - SU(3) symmetry, and 168-17870Yb possess SU(3) symmetry. The study's outcomes show that the IVBM is dependable and useful for nuclear physics research because it aligns well with the corresponding experimental data.